Association of adipokines and joint biomarkers with cartilage-modifying effects of weight loss in obese subjects. Issue 3 (March 2015) - King, L.K.; Henneicke, H.; Seibel, M.J.; March, L.; Anandacoomarasmy, A.
Summary: Objectives: To determine (1) the effects of weight loss in obese subjects on six adipokines and joint biomarkers; and (2) the relationship between changes in these markers with changes in cartilage outcomes. Design: Plasma levels of adiponectin, leptin, IL-6, COMP, MMP-3 and urine levels of CTX-II were measured at baseline and 12 months from 75 obese subjects enrolled in two weight-loss programs. Magnetic resonance imaging (MRI) was used to assess cartilage volume and thickness. Associations between weight loss, cartilage outcomes and markers were adjusted for age, gender, baseline BMI, presence of clinical knee OA, with and without weight loss percent. Results: Mean weight loss was 13.0 ± 9.5%. Greater weight loss percentage was associated with an increase in adiponectin (β = 0.019, 95% CI 0.012 to 0.026, ) and a decrease in leptin (β = −1.09, 95% CI −1.37 to −0.82). Multiple regression analysis saw an increase in adiponectin associated with reduced loss of medial tibial cartilage volume (β = 14.4, CI 2.6 to 26.3) and medial femoral cartilage volume (β = 18.1, 95% CI 4.4 to 31.8). Decrease in leptin was associated with reduced loss of medial femoral volume (β = −4.1, 95% CI −6.8 to −1.4) and lateral femoral volume (β = −1.8, 95% CI −3.7 to 0.0). When weight loss percent was included in the model, only the relationships between COMP and cartilage volume remained statistically significant. Conclusions: Adiponectin and leptin may be associated with cartilage loss. Further work will determine the relative contributions of metabolic and mechanical factors in the obesity-related joint changes.